Older adults lack SARS CoV-2 cross-reactive T lymphocytes directed to human coronaviruses OC43 and NL63 - Saletti, Giulietta; Gerlach, Thomas; Jansen, Janina M.; Molle, Antonia; Elbahesh, Husni; Ludlow, Martin; Li, Wentao; Bosch, Berend-Jan; Osterhaus, Albert D. M. E.; Rimmelzwaan, Guus F. (Scientific reports, 2020)
Currently, infections with SARS-Coronavirus-2 (SARS-CoV-2), the causative agent of the COVID-19 pandemic, are responsible for substantial morbidity and mortality worldwide. Older adults subjects > 60 years of age account for > 95% of the over one million fatal cases reported to date. It is unclear why in this age group SARS-CoV-2 infection causes more severe disease than in young adults. We hypothesized that differences in SARS-CoV-2 cross-reactive cellular immunity induced after infection with human coronaviruses (HCoVs), like OC43 and NL63, were at the basis of the differential mortality (and morbidity) observed after SARS-CoV-2 infection, because a small proportion of HCoV-specific T cells cross-react with SARS-CoV-2. Our data demonstrate that pre-existing T cell immunity induced by circulating human alpha- and beta-HCoVs is present in young adult individuals, but virtually absent in older adult subjects. Consequently, the frequency of cross-reactive T cells directed to the novel pandemic SARS-CoV-2 was minimal in most older adults. To the best of our knowledge, this is the first time that the presence of cross-reactive T cells to SARS-CoV-2 is compared in young and older adults. Our findings provide at least a partial explanation for the more severe clinical outcome of SARS-CoV-2 infection observed in the elderly. Moreover, this information could help to design efficacious vaccines for this age group, aiming at the induction of cell-mediated immunity.